Comparative Study on Quality of Life of Strabismic and Non-Strabismic Visually Normal Adults - Shrestha, Sabina; Manoranjan, Aparajita; Shrestha, Sushan Man (Medical Journal of Shree Birendra Hospital, 2016)
Introduction: Strabismus is known to affect health related quality of life in adults. This study was conducted to compare the quality of life among strabismic and non strabismic visually normal adults. Methods: A prospective cross sectional study was conducted at Nepal Eye Hospital for two years. Fifty three adults with strabismus and fifty three adults without strabismus and normal vision were enrolled. Twenty open ended adult strabismus questionnaire (AS-20) developed by Hatt et al were used to assess the impact of strabismus on patient’s health related quality of life. All the participants reviewed AS-20 instructions for patients prior to completing the questionnaire. The overall AS-20 score was calculated as a mean of all 20 item scores. The psychosocial subscale was calculated as a mean of items 1-10 (inclusive). Function subscale was calculated as a mean of items 11-20 (inclusive).The mean overall and subscale scores were compared between strabismic patients and non-strabismic visually normal adults using Mann Whitney U test. Results: Mean overall scores decreased for patients with strabismus as compared to non strabismic visually normal adults. Mean psychosocial scale among strabismic patients and non strabismic patients was 47.53 ± 24.840 and 95.42 ± 9.631 respectively and mean function subscale among the two groups were 63.57±22.652 and 83.91±13.592 respectively. There was statistical difference in the overall score, psychosocial as well as function subscale between the strabismic and non strabismic visually normal adults (p value 0.00). Conclusion: The overall quality of life appears to be adversely affected in people with strabismus in comparison to the ones without strabismus. Strabismus, being a treatable condition, should not be ignored and corrective measures should be undertaken.